THE EFFECT OF SELF-EFFICACY AND ACADEMIC PROCRASTINATION ON STUDENT LEARNING OUTCOMES IN PROFESSIONAL ETHICS SUBJECTS AT SMK NEGERI SOUTH JAKARTA - Flaurina, Nindya; Zulaihati, Sri; Sumiati, Ati (Faculty of Economics and Business, Universitas Negeri Jakarta, 2020)
This study aims to determine the effect of self-efficacy and academic procrastination onlearning outcomes. The method used is a survey method with a correlational approach. Theaffordable population is 144 students and the sample is 105 students. Data collection usingquestionnaire and documentation instruments. Based on the results of the study, it can beconcluded that there is a positive effect of self-efficacy and a negative effect of academicprocrastination together have a significant effect on learning outcomes.